Efektivitas Model Silvofishery Dalam Rehabilitasi Mangrove Di Tambak Masyarakat Muara Gembong, Jawa Barat - Muhammad Nasir; Sulaeman Natsir; Yushra Yushra (Program Studi Teknik Kelautan Universitas Abdurachman Saleh Situbondo, 2025)
Mangrove ecosystems are among the most productive coastal ecosystems, providing shoreline protection, habitat for fisheries, and substantial blue-carbon storage. In Muara Gembong, Bekasi, extensive conversion of mangroves into ponds and settlements has triggered severe erosion and tidal flooding. One approach promoted to reconcile ecosystem rehabilitation and local livelihoods is the silvofishery model, which integrates mangrove planting into community ponds. This study analyses the effectiveness of the silvofishery model implemented in the Grow & Green Program in Muara Gembong based on mangrove survival rate and conformity of planting design with technical silvofishery criteria. A descriptive quantitative approach was applied using secondary data from the 2023 program report, including planting design, number of seedlings, pond area, and three monitoring cycles in seven community ponds. Planting used a kao–kao pattern forming a greenbelt along pond dikes with Rhizophora mucronata seedlings at 1 × 1 m spacing. Results show that mangrove survival reached about 83.73% in the first monitoring and increased to nearly 90% in the third monitoring after regular replanting and maintenance. The design met key technical criteria, including integration with pond aquaculture and adequate tree density per hectare. Main constraints were leaf-eating insects, prolonged dry season, and suboptimal water circulation. Overall, the silvofishery model in the Grow & Green Program can be categorized as effective in supporting early-phase mangrove rehabilitation while maintaining the economic function of community ponds in Muara Gembong.